2018
DOI: 10.1177/1538574418798418
|View full text |Cite
|
Sign up to set email alerts
|

Open Versus Endovascular Repair of Isolated Iliac Artery Aneurysms

Abstract: Iliac artery aneurysmss can be safely and effectively treated by EVIR or OIR regarding 30-day morbidity, mortality, and long-term survival, although freedom from reintervention is significantly lower after EVIR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 43 publications
(67 reference statements)
0
19
0
Order By: Relevance
“…Wound complications were reported in 4 studies including wound infection and healing disorder. 14,15,17,18 The pooled meta-analysis showed no difference between groups in wound complications (OR: 0.52, 95% CI: 0.20-1.36; Figure 4).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Wound complications were reported in 4 studies including wound infection and healing disorder. 14,15,17,18 The pooled meta-analysis showed no difference between groups in wound complications (OR: 0.52, 95% CI: 0.20-1.36; Figure 4).…”
Section: Resultsmentioning
confidence: 96%
“…Postoperative ischemic complications were defined as ischemic symptoms that related to the procedure, such as buttock claudication, bowel ischemia, and erectile dysfunction. Five of the included studies reported the outcome of PICs, 10,14,15,17,18 none of them reported a significant difference between groups. However, the pooled forest plots showed that compared with OS, ET was associated with a higher risk of PICs (OR: 3.24, 95% CI: 1.05-10.02; Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 However, OR demonstrated comparable 1-and 5-year overall mortality with significantly higher freedom from reintervention than ER. 12 However, it may be possible that decreasing exposure to open aortoiliac surgery both in training and in practice may have an impact on a vascular surgeon's willingness to offer OR when ER options exist. 13 Thus, healthy patients with longer life expectancy would benefit from OR, free from an intensive lifelong surveillance program.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that aneurysms located deep in the pelvic cavity are very difficult to treat surgically, and the operations to do so have high mortality rates . In the other hand, it has reported that isolated iliac artery aneurysm can be can be safely and effectively treated by open repair or endovascular repair . Moreover, if rupture has occurred, the urgency of the patient's condition, their hemodynamics, and the presence of retroperitoneal hematoma can further complicate the open procedure.…”
Section: Discussionmentioning
confidence: 99%